Air Pollution: A Neglected Risk Factor for Dementia in Latin America and the Caribbean - Santos, Nathália Villa dos; Yariwake, Victor Yuji; Marques, Karina do Valle; Veras, Mariana Matera; Fajersztajn, Laís (Frontiers in Neurology, 2021)
The burden of dementia in Latin America & the Caribbean (LAC) is high and will increase in the coming years. Currently, at least 172 million people breathe unhealthy levels of air pollution in this region. Several cohort studies have indicated that air pollution increases the risk of developing dementia, but the mechanisms underlying the association are still not clear. Air pollution causes and aggravates five established risk factors for dementia: obesity, hypertension, stroke, diabetes mellitus, and heart diseases. It has also been linked to three other factors: physical inactivity, cognitive inactivity, and depression). Some of these could be mediating the association between air pollution and dementia. However, the direct effect of air pollution on the brain cannot be ruled out. Reducing risks for dementia is crucial and urgently needed in LAC countries. There is room for improving air quality in many urban areas in the LAC region and other low-and-middle-income countries (LMICs). This is already being explored in developing regions. Moreover, reducing air pollution has been proven to enhance health outcomes. There is an ongoing and valid scientific discussion about whether air pollution can or cannot directly affect the brain and cause or aggravate dementia. In this article, we present air pollution as a potentially modifiable risk factor for dementia in the LAC region and possibly in other LMICs. Controlling and reducing current air pollution levels in these regions could strongly contribute to reducing the high burden of dementia cases that has been projected for these countries.